Isolation and Purification of Thiamine Binding Protein from Mung Bean - GUNARTI, DWIRINI RETNO; RAHMI, HANIFAH; SADIKIN, MOHAMAD (HAYATI Journal of Biosciences, 2013)
Thiamine has fundamental role in energy metabolism. The organs mostly sensitive to the lack of thiamine levels in the body are the nervous system and the heart. Thiamine deficiency causes symptoms of polyneuritis and cardiovascular diseases. Because of its importance in the metabolism of carbohydrates, we need to measure the levels of thiamine in the body fluids by using an easy and inexpensive way without compromising the sensitivity and selectivity. An option to it is thiamine measurement based on the principle of which is analogous to ELISA, in which a thiamine binding protein (TBP) act by replacing antibodies. The presence of TBP in several seeds have been reported by previous researchers, but the presence of TBP in mung beans has not been studied. This study was aimed to isolate and purify TBP from mung bean. The protein was isolated from mung bean  through salting out by ammonium sulphate of 40, 70, and 90% (w/v). TBP has a negative charge as shown by cellulose acetate electrophoresis. The result obtained after salting out by ammonium sulphate was further purified bymeans of DEAE-cellulose chromatography and affinity chromatography. In precipitation of 90% of salting out method, one peak protein was obtained by using affinity chromatography. The protein was analyzed by SDS PAGE electrophoresis. The result of SDS PAGE electrophoresis showed that TBP has a molecular weight of 72.63 kDa.